STAGES IN EDITING OF EKA SABARA’S DAENG NACHODA MANUSCRIPT - Ni Ketut Mirahayuni (Universitas 17 Agustus 1945 Surabaya, 2019)
Documentation of important historical figures and events in manuscript for publication involves editing, both for the content and language. This article reports a study of editing of Eka Sabara’s manuscript of Daeng Nachoda, an important figure in the founding and development of the Buginese-Makassar moslem community in Loloan, Jembrana Regency, Bali, Indonesia. Following Blanchard and Root’s (1997) points on editing written text, this study aims at analyzing the manuscript’s editing process. The problems are: the characteristics of the manuscripts and necessary editing stages for its preparation for publication. Adopting a qualitative descriptive research design, the study focuses on the content analysis of the manuscript. The result of the study shows that the manuscript shows two major characteristics: information and language structure. The study also shows that the manuscript editing processes includes addition, reduction and re-arrangement of information and structure. This study contributes to more insights of pre-printing manuscript processing.